A Tribute to Marty Taubman: The Earl of Sandwich, IgA, T-regs, and the Celtics. (March 2014) - Genco, R.J.
This tribute to Marty Taubman is written on the occasion of his retirement from full-time faculty status at The Forsyth Institute and Harvard Dental School, and his stepping down as editor of the "Discovery!" section of the Journal of Dental Research . It recognizes his seminal contributions to oral immunology, his mentoring of a generation of new scientists, his key role as a leader in organized research as president of the American Association for Dental Research, as well as his editorship, which has recognized scores of his colleagues in science. He is a leader in our field and has made many lasting contributions to research, teaching, and our profession, for which we are very grateful.